Direct Release of Sombrero‐Shaped Magnetite Nanoparticles via Nanoimprint Lithography. Issue 3 (10th January 2015) - Kwon, Byung Seok; Zhang, Wei; Li, Zheng; Krishnan, Kannan M.
<x xml:space="preserve">Abstract</x> Magnetic nanoparticles produced via nanoimprint lithography can change the current paradigm of fabrication processes from chemical "bottom‐up" synthesis to "top‐down" fabrication. The combination of controlled nondirectional magnetron sputtering, ETFE mold, bilayer lift‐off, and dry etching release can control the shape, size, and structure of the fabricated nanoparticles. The resulting magnetic nanoparticles have a novel "sombrero" shape with complex and unique physical/magnetic properties. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>